Assessing the performance of GPS tomography at retrieving water vapour fields during landfalling atmospheric rivers over southern California. (24th August 2020) - Chen, Biyan; Yu, Wenkun; Dai, Wujiao; Wu, Hao; Wang, Wei
Abstract: Accurate monitoring of water vapour evolution is essential to gain a better understanding of the atmospheric river movement, as well as predicting the severity and life cycle of heavy precipitation. The use of hundreds of ground Global Positioning System (GPS) stations in southern California provided a good opportunity to monitor the water vapour changes associated with landfalling atmospheric rivers. Based on a tomographic technique, the 15 min‐resolution water vapour density fields of southern California were reconstructed for February 2019. The assessments by radiosonde and the European Centre for Medium‐Range Weather Forecasts' (ECMWF) Re‐Analysis Interim (ERA‐Interim) database reanalysis show that tomography can retrieve the density profiles with an overall accuracy of about 1.1 g·m –3 . In addition, both assessments indicate that the tomographic solutions of altitudes > 6 km are not reliable as relative root mean square error can reach up to 500% in the uppermost layer. Nevertheless, tomographic integrated water vapour is consistent with those derived from radiosonde and ERA‐Interim because their discrepancies are basically < 3 mm. The tomographic density fields were then applied to monitor water vapour evolution associated with two atmospheric river landfalls that occurred on February 2 and February 13, 2019. Results show that both atmospheric rivers made landfall from the northwest and passed over southern California in a southeasterly direction. The series of density profiles reveals that the high‐elevation mountains can block the atmospheric river movement, resulting in the concentration of water vapour at the foot of the mountains. Abstract : The dense global navigation satellite system (GNSS) network of southern California can reconstruct tomographically the water vapour density fields with an overall accuracy of about 1.1 g·m –3 . Three‐dimensional structures of the water vapour fluctuation associated with two atmospheric rivers movement were examined. Tomographic density profiles can reveal the three‐dimensional water vapour evolution caused by the atmospheric river movement.